From emergence to extinction: the trajectory of an outpatient medical genetics service in Brazil - Abreu, Tatiane; Liberato, Érica; Marsiglio, Heloisa; Santos, Thamires; Ortensi, Natália; Barbosa, Calógeras; Melo, Débora (Journal of Health Care, 2021)
Introduction: The number of health professionals involved in specialized care in genetics is considered insufficient in Brazil, and it is assumed that most patients and families do not receive adequate care. Also, the availability of human and material resources for care in genetics is very uneven in various regions of the country. Objectives: To describe the trajectory of an outpatient medical genetics service in Brazil and to highlight the importance of organizing the medical genetic care network in this country. Methodology: Quantitative, cross-sectional, and retrospective study, in which the care maps of all 792 patients evaluated at Medical Genetics Outpatient Clinic in São Carlos, São Paulo, from June 2006 to December 2018 were reviewed. Results: There was a great diversity of genetic diseases, which affect people in different age groups. A genetic diagnosis was defined in 290 patients (36.6%) and ruled out in 153 patients (19.3%); 23 patients (2.9%) received genetic counseling for future offspring and in 326 patients (41.2%) a genetic diagnosis was neither defined nor ruled out. The frequency of unresolved cases explains difficulties inherent to clinic genetic diagnosis and barriers to access molecular genetic tests. Conclusion: Experiences such as Medical Genetics Outpatient Clinic in São Carlos show the obstacles to providing adequate health services to the population in genetics, reinforcing the need to organize the genetic care network in the Brazilian Unified Health System, based on the National Policy for Comprehensive Care for People with Rare Diseases.